P-41 Case report: unusual visualisation of oxycontin ghost tablets. (20th March 2022) - Walsh, Maria; Hayes, Leah; Cooney, Mary; Jacob, Prem; Myles, Helena; Twomey, Feargal
Abstract : Background: The concept of 'ghost pills' is well described in the literature. The term refers to extended-release medications that allow absorption of the active ingredients while the outer layer (or shell) is passed intact in the stool. The appearance of these ghost pills can cause distress for both patients and clinicians unfamiliar with the phenomenon. Case Presentation: A 52 year old man presented with unintentional weight loss and passing urine per rectum. Investigations revealed bladder SCC with invasion of the left pelvic side-wall and colo-vesical fistula. He was referred to the specialist palliative care team for symptom management and prescribed OxyContin 80 mg BD along with PRN Oxynorm. He underwent defunctioning stoma and urinary catheter insertion. A subsequent cystoscopy visualised OxyContin tablets within the bladder, clearly demarcated with '20 mg'. Concerns were raised that the patient was not absorbing his analgesia. Management and Outcomes: Analgesia had been titrated in the days preceding the cystoscopy with good effect. The concept of 'ghost tablets' was discussed with the primary team and the patient, and reassurance provided. The patient went on to complete 40Gy (15#'s) palliative radiotherapy. He died prior to commencing chemotherapy. Discussion: Ghost tablet visualisation in stool passed per rectum or via stoma is not uncommon. In this case, the colo-vesical fistula allowed the passage of the tablet shell to enter the bladder resulting in an unexpected finding on cystoscopy. Lack of awareness regarding the mechanism of action of extended-release medications may cause concern for patients and staff around perceived drug malabsorption. Conclusion: Education around the existence of ghost tablets among the wider medical and surgical community is important in order to prevent undue anxiety and unnecessary alterations to analgesia regimens.